صورة نجيب محفوظ بين مجتمع القارئين في جوكجاكرتا (دراسة استقبالية أدبية) / The Portrayal of Najib Mahfudz Among the Readers Qari’ Community in Yogyakarta (Literary Reception Study) - Dyah Nurul Azizah; Muslim Yanuar Sugrindo As-Salafi; Tatik Mariyatut Tasnimah (Diwan : Jurnal Bahasa dan Sastra Arab, 2022)
نجيب محفوظ هو روائي مصرى كبير واشتهر بأبي الروايات العربية الحديثة. وقد حاز على جائزة نوبيل عام 1988 من قبل المجتمع الغربي بإنجازاته الجمالية وتعاطفه الإنسانية بين روائعه الأدبية. كان الدافع لظهور جميع روائعه هو اهتمامه بمشاكل المجتمع وسعيه لمحاولة بناء المجتمع الجديد. ومع ذلك، اقترض بعض المجتمع أن روائعه مثيرة للجدل وقد حصل عليه النقد السلبي والتجديف نحو الجوانب الدينية. بذلك وصل الباحثون على الإثبات أن الروائع الأدبية لنجيب محفوظ تثير أنواع الردود والتعليقات من مختلف المجتمع. تهدف هذه الدراسة للكشف عن استجابة القارئين الباحثين في جوكجاكرتا خاصة لروائع نجيب محفوظ الأدبية. استخدم الباحثون النظرية الاستقبالية الأدبية التي تقيم القارئين كأهم العامل من العوامل المؤثرة لكشف صورة الأديب الروائي المذكور من بين أنواع روائعه. وكان المنهج المستخدم في هذا البحث هو المنهج الكيفي لاستنباط استقبال وتلقي القارئين الباحثين نحو الروائي وروائعه الأدبية. والنتيجة المؤقتة عن استقبال القارئين الباحثين في منطقة جوكجاكرتا توصلت إلى أربعة نقط، هي: أولا، أنه كرائد الحداثة، ثانيا أنه كمؤيد حركة النسوية، ثالثا أنه كحامل الايديولوجية العلمانية، ورابعا أنه كمؤلف الرواية السيكولوجية. الكلمات المفتاحية : نجيب محفوظ؛ الاستقبالية الأدبية؛ مجتمع القراء بجوكجاكرتا Abstract Najib Mahfuz is a great novelist of Egyptian descent who is known as the Father of Modern Arabic Novels. He was awarded the Nobel Prize in 1988 in recognition of his aesthetic achievements and humanitarian significance to Western society. The birth of his literary works was motivated by his concern for the problems of society in its transformation into a modern society. However, some of his works were considered controversial and received negative criticism, even blasphemy, in the religious aspect. Najib Mahfuz's works have elicited a wide range of reactions from various audiences. The purpose of this research is to discover the reactions of Yogyakarta-based researchers to these works. The writer applied the theory of literary reception, which is a theory that sees the reader's role as an important factor in literary interpretation. The method used is the critical method, which is the method used in analyzing research such as scientific works, theses, and dissertations to get reception or response to a literary work. The conclusion of the study is that of Najib Mahfudz as a pioneering figure of modernity, a supporter of the feminist movement, a carrier of secular ideology, and the author of psychological novels.